The Small Molecule P7C3-A20 Exerts Neuroprotective Effects in a Hypoxic–ischemic Encephalopathy Model via Activation of PI3K/AKT/GSK3β Signaling. (10th August 2020) - Bai, Junjie; Zeng, Shanshan; Zhu, Jinjin; Fu, Changchang; He, Minzhi; Zhu, Jianghu; Chen, Shangqing; Fu, Xiaoqin; Li, Peijun; Lin, Zhenlang
Highlights: P7C3-A20 could decrease brain atrophy and alleviate apoptosis after HI injury. P7C3-A20 could improve the prognosis after HI injury. P7C3-A20 has not been found toxic effects on other organs of newborn rats. P7C3-A20 exerted neuroprotection via the PI3K/ Akt/GSK3β pathway. Abstract: Hypoxic–ischemic encephalopathy (HIE) in neonates can lead to severe long-term disabilities including cerebral palsy and brain injury. The small molecule P7C3-A20 has been shown to exert neuroprotective effects in various disorders such as ischemic stroke and neurodegenerative diseases. However, it is unclear whether P7C3-A20 has therapeutic potential for the treatment of HIE, and the relationship between P7C3-A20 and neuronal apoptosis is unknown. To address these questions, the present study investigated whether P7C3-A20 reduces HI injury in vitro using a PC12 cell oxygen-glucose deprivation (OGD) model and in vivo in postnatal day 7 and 14 rats subjected to HI, along with the underlying mechanisms. We found that treatment with P7C3-A20 (40–100 µM) alleviated OGD-induced apoptosis in PC12 cells. In HI model rats, treatment with 5 or 10 mg/kg P7C3-A20 reduced infarct volume; reversed cell loss in the cortex and hippocampus and improved motor function without causing neurotoxicity. The neuroprotective effects were abrogated by treatment with the phosphatidylinositol 3-kinase (PI3K) inhibitor LY294002. These results demonstrate that P7C3-A20 exerts neuroprotection by activating PI3K/protein kinase B/glycogen synthase kinase 3β signaling and can potentially be used to prevent brain injury in neonates following HIE.